Primary care physicians’ satisfaction after health care reform: a cross-sectional study from two cities in Central Java, Indonesia - Maharani, Chatila; Marx, Michael; Loukanova, Svetla (BMC health services research, 2019)
In 2014, Indonesia launched a mandatory national health insurance system called Jaminan Kesehatan Nasional (JKN). The reform introduced new conditions for primary care physicians (PCPs) that could influence their job satisfaction. This study assessed PCPs’ satisfaction and its predictors in two cities in Central Java, Indonesia, following the reform.
Gesehen am 02.08.2019